Meta Analysis Study: The Effect of Mind Mapping on Students' Multiple Intelligence - Didi Haryanto; Tomi Apra Santosa; Evy Lalan Langi; Hersiyati Palayukan; Ika Agustina (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effect size of mind mapping learning model on students' multiple intelligence. This research is a meta-analysis. The sample came from 15 national and international journals. The process of searching for data sources in this study through Google Scholar, ScienceDirect, Wiley and ProQuest. The inclusion criteria used are journals or proceedings indexed by Scopus, SINTA, DOAJ and Web of Science; 2) Has mind mapping and multiple intelligence variables; 3) The type of research is experimental or quasi-experimental; 4) has mean, standard deviation and t value data. Data collection is done by direct observation and documentation. Data analysis was carried out by calculating the effect size value and standard deviation with the help of JSAP application. The results of this study show that the average effect size value is 0.871 with high criteria. This finding shows that mind mapping learning has an influence on students' multiple intelligence in learning. Mind mapping learning helps students better remember the learning material that has been learned.